(untitled) (BIRDEM Medical Journal, 2020)
Background: Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection emerged in Wuhan, China in December 2019 and rapidly became pandemic. Unfortunately, there is a lack of evidence about the optimal management of corona virus disease-2019 (COVID-19) and even less is available in patients on maintenance haemodialysis than general population. So, the purpose of this study was to identify the incidence of SARS-CoV-2 infection among end-stage kidney disease (ESKD) patients in a haemodialysis unit in tertiary care hospital of Bangladesh. Methods: A cross-sectional study was conducted at haemodialysis unit of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from April to August 2020. All patients, who were on maintenance haemodialysis, twice or thrice weekly, were screened by reverse transcriptase-polymerase chain reaction (RT-PCR) for SARS-CoV-2, irrespective of symptoms. All data were collected in case record forms and discharged/referred patients were followed-up over phone. Results: During the study period, a total of 133 patients (males 70, 52.6%) were on regular maintenance haemodialysis in the study center. Most patients were in 5th and 6th decades of life. Twenty-one (15.8%) patients tested positive for SARS-CoV-2 by RT-PCR with female (16, 76.2%) predominance. Eighteen (18/21, 85.7%) patients had symptoms suggestive of SARS-CoV-2 infection and rest three (3/21, 14.3%) patients were diagnosed during routine screening. Common presentations were fever (42.9%), cough (66.7%) and respiratory distress (66.7%) and most had multiple symptoms. Blood group A (38%) and O (38%) showed the higher incidence of SARS-CoV-2 infection than blood group B and AB with equal mortality rate among them. Most patients (16/ 21, 76.2%) infected by SARS-CoV-2 were referred to COVID-dedicated hospitals, five (5/21, 23.8%) were shifted to intensive care unit (ICU) of BIRDEM General Hospital. Outcome was poor; 17 (17/21, 89%) patients died in hospitals and four (4/21, 19%) patients became free of SARS-CoV-2 infection. Caregivers/relative of four patients acquired COVID-19 in course of disease. Conclusion: One-sixth of patients on maintenance haemodialysis acquired SARS-CoV-2 infection with nearly ninety percent fatality rates. Despite having risk factors for severe infection by SARS-CoV-2, dialysis patient must visit health care facilities. So, utmost care should be taken to reduce risk of COVID-19 among such vulnerable group of patients. Birdem Med J 2020; 10, COVID Supplement: 41-45